KOMBINASI PREDIKSI VOLUME SEDIMEN MENGGUNAKAN METODE HECRAS-USLE UNTUK MENDUKUNG KONSERVASI DAS LAMBIDARO PALEMBANG, SUMATERA SELATAN - Masri nur Sultan; Mohammad Farid; Adi Prasetyo; Muhammad Syahril Badri Kusuma; Dantje Kardana Natakusumah (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2023)
ABSTRACT Over the past ten years, flooding has been the most frequent problem in South Sumatra Province, Indonesia. As the capital of South Sumatra Province, Palembang City faces similar problems, where Lambidaro Watershed is the watershed with the highest 25-year potential flood discharge in Palembang City. One of the causes of flooding is the lack of river channel capacity related to land erosion in the watershed. This study aims to learn the prediction of sediment volume and efforts to reduce it in the Lambidaro watershed, Palembang City. This study uses two types of modeling, namely numerical models and empirical models. The numerical model uses the HEC-RAS 6.3.1 application, while the empirical model uses the USLE and SDR equations. The input parameters of the numerical model use some data derived from field measurements. The sediment concentration and observation discharge parameters were measured three times in September 2022. The grain size distribution parameters were sampled at three locations each once in August 2022, and the cohesive parameter was sampled at one location twice in August 2022. The result of the prediction of sediment volume by the numerical model is 1,421.86 m3/year. In contrast, the result of the prediction by the empirical model is 476,941.25 m3/year. Efforts to reduce the prediction of sediment volume USLE method are in the form of applying the intercropping method. The results of the conservation study show that the efforts made can reduce the volume of sediment by 17%.Keywords: sediment, flood, conservation, intercropping, Lambidaro, ABSTRAKSelama sepuluh tahun terakhir, banjir telah menjadi masalah yang paling sering terjadi di Provinsi Sumatera Selatan Indonesia. Sebagai ibu kota provinsi Sumatera Selatan, kota Palembang menghadapi masalah serupa. dimana DAS Lambidaro adalah DAS dengan potensi debit banjir kala ulang 25 tahun tertinggi di kota Palembang. Salah satu penyebab banjir adalah penurunan kapasitas alur sungai yang berkaitan dengan erosi lahan di DAS. Penelitian ini bertujuan untuk melakukan kajian prediksi volume sedimen serta upaya pengurangannya di DAS Lambidaro. Penelitian ini menggunakan dua jenis pemodelan yaitu model numerik dan model empirik. Model numerik menggunakan aplikasi HEC-RAS 6.3.1 sedangkan model empirik menggunakan persamaan USLE dan SDR. Parameter input dari model numerik menggunakan beberapa data yang berasal dari pengukuran lapangan. Parameter konsentrasi sedimen dan debit sesaat diukur sebanyak tiga kali pada bulan September tahun 2022. Parameter gradasi butiran diambil sampelnya masing – masing pada tiga lokasi sebanyak satu kali, dan parameter kohesif diambil sampelnya pada satu lokasi sebanyak dua kali pada bulan Agustus tahun 2022. Hasil prediksi sedimentasi dasar sungai model numerik adalah 1.421,86 m3/tahun sedangkan hasil prediksi volume sedimen model empirik adalah 476.941,25 m3/tahun. Upaya mengurangi prediksi volume sedimen metode USLE berupa penerapan metode tumpang-sari. Hasil kajian konservasi menunjukkan upaya yang dilakukan dapat mengurangi volume sedimen sebesar 17%.Kata Kunci: sedimen, banjir, konservasi, tumpang-sari, Lambidaro